GAMBARAN RASIO NEUTROFIL IMATUR/NEUTROFIL TOTAL (RASIO I/T) PADA TERSANGKA SEPSIS NEONATORUM YANG DIRAWAT DI INSTALASI PERAWATAN NEONATUS RSUD ARIFIN ACHMAD PROVINSI RIAU - Reslina, Ade Novita; ", Fatmawati; Wisnumurti, Dewi A (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBackground: Neonatal sepsis is one of major cause of neonatal death in developing countries. Blood culture is gold standard to diagnose sepsis neonatorum, but it needed 3-5 days for the result. Early diagnostic and approriate treatment can reduce the mortality and morbidity of patients. Immature to total neutrophil ratio (I/T ratio) can be used as early marker for diagnosis of neonatal sepsis.Objective: This study aimed to know I/T ratio of suspected neonatal sepsis treated in the Neonatal Unit of Arifin Achmad General Hospital of Riau Province.Methods: This is study was conducted using descriptive retrospective methods during February 2015. The sample were collected by consecutive sampling. Results: We found that 97 suspected neonatal sepsis, 81,5% of whom were 0-6 days old, 56,7% were males, and 48,5% had gestational age < 37 weeks. Late onset sepsis was the highest classification of sepsis at 80% from 30 cases of neonatal sepsis. Immature to total neutrophil ratio on suspected neonatal sepsis was ≥ 0,2 (50,5%) with a median value is 0,2.Conclusion: There was a increased I/T ratio on suspected neonatal sepsis.Keywords: sepsis, neonate, I/T ratio